Abdominal symptoms in general practice: Frequency, cancer suspicions raised, and actions taken by GPs in six European countries. Cohort study with prospective registration of cancer. Issue 6 (June 2017) - Holtedahl, Knut; Vedsted, Peter; Borgquist, Lars; Donker, Gé A.; Buntinx, Frank; Weller, David; Braaten, Tonje; Hjertholm, Peter; Månsson, Jörgen; Strandberg, Eva Lena; Campbell, Christine; Ellegaard, Lisbeth; et al.
Abstract: Background: Abdominal symptoms are diagnostically challenging to general practitioners (GPs): although common, they may indicate cancer. In a prospective cohort of patients, we examined abdominal symptom frequency, initial diagnostic suspicion, and actions of GPs in response to abdominal symptoms. Methods: Over a 10-day period, 493 GPs in Norway, Denmark, Sweden, Belgium, the Netherlands, and Scotland, recorded consecutive consultations: sex, date of birth and any specified abdominal symptoms. For patients with abdominal symptoms, additional data on non-specific symptoms, GPs' diagnostic suspicion, and features of the consultation were noted. Data on all cancer diagnoses among all included patients were requested from the GPs eight months later. Findings: Consultations with 61802 patients were recorded. Abdominal symptoms were recorded in 6264 (10.1%) patients. A subsequent malignancy was reported in 511 patients (0.8%): 441 (86.3%) had a new cancer, 70 (13.7%) a recurrent cancer. Abdominal symptoms were noted in 129 (25.2%) of cancer patients ( P < 0.001), rising to 34.5% for the 89 patients with cancer located in the abdominal region. PPV for any cancer given any abdominal symptom was 2.1%. In symptomatic patients diagnosed with cancer, GPs noted a suspicion of cancer for 85 (65.9%) versus 1895 (30.9%) when there was no subsequent cancer ( P < 0.001). No suspicion was noted in 32 (24.8%) cancer patients. The GP's intuitive cancer suspicion was independently associated with a subsequent new cancer diagnosis (OR 2.11, 95% CI 1.15–3.89). Laboratory tests were ordered for 45.4% of symptomatic patients, imaging for 10.4%, referral or hospitalization for 20.0%: all were more frequent in subsequent cancer patients ( P < 0.001). Interpretation: Abdominal symptoms pointed to abdominal cancers rather than to other cancers. However, the finding of abdominal symptoms in only one third of patients with an abdominal cancer, and the lack of cancer suspicion in a quarter of symptomatic cancer patients, provide challenges for GPs' diagnostic thinking and referral practices.